Immobilization of Crude Polyphenol Oxidase Extracts from Apples on Polypyrrole as a Membrane for Phenol Removal - Anceu Murniati; Buchari Buchari; Suryo Gandasasmita; Zeily Nurachman; Arie Hardian; Dera Triani (Jurnal Kimia Sains dan Aplikasi, 2021)
This research aims to make a polypyrrole (PPy) membrane and crude extract of polyphenol oxidase (PPO) as a membrane of mPPy/PPO apple extracts. The membrane of PPy/PPO-apple extract has been synthesized by the electrodeposition method. The electrolyte composition consists of a mixture of 0.10-0.20 M pyrrole (Py) and 50-100% PPO apple extract, which is stable using 50 mM of phosphate buffer solution at pH 6.80-7.00 and room temperature. The electrodeposition process is used 400 mesh steel gauze anode ST-304 and carbon plate cathode. Electrodeposition is carried out at potential = 5.00-6.00 V; current = 0.02-0.25 A; the distance from both electrodes = 1.00-2.00 cm for 300-500 seconds. The results from the deposition of PPy/PPO apple extract of the anode are a membrane of mPPy/PPO-apple extract, with total enzyme activity (U) = (957,1441, 2287 and 1754) using 2.00-5.00 mM phenol as a substrate which is measured based on the UV-visible spectrophotometric method. PPy and mPPy/PPO-apple extracts were characterized by SEM and SEM-EDS. The membrane of mPPy/PPO-apple extract can be used to remove phenol in industrial wastewater samples is 50-65% with a filtration capacity of 500 mL for 2 hours.